2021
DOI: 10.1101/2021.01.25.428100
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcranial direct current stimulation does not improve performance in a whole-body movement task

Abstract: Research has investigated the use of non-invasive brain interventions, such as transcranial direct current stimulation (tDCS), to enhance motor learning and rehabilitation. Much research has shown that tDCS improves motor learning and that bilateral tDCS is more beneficial than unilateral tDCS in improving motor learning. However, past research has primarily utilised simple motor tasks in measuring motor skill learning. These are not ecologically reliable as whole-body movement is required for everyday activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…17 However, people with low emotional self-regulation suffer from feelings of selfdoubt, loss of control and failure. 18 Previous research has shown the relationship between emotional self-regulation with psychological well-being and emotional-social adjustment, 19 depression and anxiety. 20 Since cognitive flexibility and emotional self-regulation are among the components that can have a significant impact on the psychological health and psychological well-being of the elderly with ENS and can increase their adjusting, paying attention to solutions of increasing self-regulation and flexibility is of great importance, emphasizing on providing psychological plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, people with low emotional self-regulation suffer from feelings of selfdoubt, loss of control and failure. 18 Previous research has shown the relationship between emotional self-regulation with psychological well-being and emotional-social adjustment, 19 depression and anxiety. 20 Since cognitive flexibility and emotional self-regulation are among the components that can have a significant impact on the psychological health and psychological well-being of the elderly with ENS and can increase their adjusting, paying attention to solutions of increasing self-regulation and flexibility is of great importance, emphasizing on providing psychological plans.…”
Section: Introductionmentioning
confidence: 99%
“…17 However, people with low emotional self‐regulation suffer from feelings of self‐doubt, loss of control and failure. 18 Previous research has shown the relationship between emotional self‐regulation with psychological well‐being and emotional‐social adjustment, 19 depression and anxiety. 20 …”
Section: Introductionmentioning
confidence: 99%